A imagem do outro na Crónica da Tomada de Ceuta pelo Rei D. João I de Gomes Eanes de Zurara - Natália Albino Pires (Medievalista)
The representation of the Other is as old as the cultural history of humanity and the image that is portrayed of that Other depends entirely on the I that describes and builds it. Thus, based on the theoretical assumptions of imagology, we aim at analysing the image of the moors as depicted on the Chronicle of the Conquest of Ceuta, seeking to track the topos of the Portuguese praise, cornerstone of the construction of national identity.